Needs Analysis of English for Specific Purposes for Occupational Health and Safety Students in Higher Education - Eka Indah Nuraini; Hesti Rokhaniyah; Muhammad Faiz Al-Fikry (Wanastra: Jurnal Bahasa dan Sastra, 2026)
This study aims to identify the English for Specific Purposes (ESP) learning needs of students majoring in Occupational, Health, and Safety (OHS) in order to design relevant teaching materials. This study employed a survey design involving 30 OHS students and an ESP instructor at Darussalam Gontor University. Data was collected through questionnaires and semi-structured interviews, then analyzed using descriptive statistics and qualitative analysis. The findings indicate that students strongly prefer communication-oriented learning, particularly speaking skills for workplace interactions, and emphasize the importance of mastering vocabulary related to OHS. However, current ESP teaching materials are considered inadequate due to their limited relevance to the specific OHS context. Students also expressed a need for contextualized teaching materials that incorporate real-life tasks, international safety standards, and performance-based assessments. In summary, this study highlights the need to develop context-specific, task-based ESP teaching materials aligned with the demands of professional communication in the OHS field. These findings provide an empirical foundation for designing an English for Occupational Health and Safety (EOHS) textbook that better supports students’ readiness to communicate in global workplaces.